A multi-level developmental approach towards understanding adolescent mental health and behaviour: rationale, design and methods of the LIFECOURSE study in Iceland ... - Halldorsdottir, Thorhildur; Kristjansson, Alfgeir L.; Asgeirsdottir, Bryndis Bjork; Thorisdottir, Ingibjorg E.; Sigfusson, Jon; Jonsdottir Tolgyes, Erla Maria; Valdimarsdottir, Heiddis; Allegrante, John P.; Sigfusdottir, Inga Dora (Columbia University, 2020)
Purpose: Identifying and understanding modifiable risk and protective factors that can inform early detection and intervention to prevent adolescent emotional problems and harmful behaviours is among the most pressing modern-day public health challenges. This paper describes the rationale, objectives, methods, and anticipated outcomes of the LIFECOURSE study, a multi-level, bio-psychosocial prospective study designed to advance our understanding of factors that shape adolescent mental health and behaviour. Methods: Conducted by the Icelandic Centre for Social Research and Analysis at Reykjavik University, LIFECOURSE is a longitudinal population-based developmental study of Icelandic adolescents born in 2004. The study utilizes a comprehensive multi-informant assessment of individual, societal and biological factors measured across the lifespan. Data assembly and collection were conducted from 2016-2020 and utilize both retrospective and prospective data sources: (a) retrospective registry data assembled from ...